The MDAB students’ reading attitudes and their academic reading performance / Affidah Morni … [et.al.] - Morni, Affidah; Alfred Tom, Amelia; Mohd Nawawi, Norlida; Wan Hassan, Sharifah Zakiah (2013)
This study is conducted to investigate MDAB students’ general reading attitudes. It also aims to discover the relationship between the students’ academic reading performance with their reading attitudes. This study sets out to determine that if students practice good reading habits, the habits will eventually help them in dealing with the ESL reading, writing and speaking components for BEL011-The Introductory English course offered to Part 1 students of Pre-Commerce Programme, thus produce favourable academic reading, writing and speaking results. At the same time, it also sets out to investigate whether the students’ academic reading performance is solely influenced by their reading attitudes or otherwise.